The examination of certain theories of human perfection in relation to their authors' valuation of human materiality. - Khatib, Michael. (University of Ottawa (Canada), 1997)
The bulk of this thesis consists in the analysis of various authors' theories of human perfection in an attempt to reveal the author's valuation of human existence, which can be put in terms of whether the author is a spiritual dualist or not. The authors which we look at consist of both, authors who seem to have a negative valuation of material existence, as well as those that seem to have a positive valuation (such as Weil, Kierkegaard and Nietzsche, as well as certain Medieval ascetic women and desert fathers). In some cases the initial appearance is shown to be correct and in some cases it is shown to be incorrect. I also provide a detailed analysis of Simone Weil's philosophy, bringing to light the positive value she placed on the material aspects of human existence in relation to man's final end. One of the conclusions of this study is that a theory of human perfection is affected by the author's anthropology. The role that the body is permitted to play in human perfection is, at least in some measure, determined by the extent to which the body is seen as being ontologically independent from the soul. This indicates that, at least with respect to the authors examined, there is a strong relationship between anthropological dualism and a negative valuation of man's material nature. But this relationship is logical or theoretical in nature and we cannot expect this logical necessity to be reflected straightforwardly in an author's work. Some authors might hold, in a contradictory way, an anthropological dualism while having a positive valuation of the body. We try to show that this contradictory stance indicates an author's conflict of values and can sometimes even be seen as leading to a movement away from anthropological dualism in the author's writings even where the conflict is not addressed explicitly. Or, an author who is, for example, an anthropological dualist while having a positive attitude towards the body might only realize the incompatibility of these positions while developing a theory of human perfection. And, thus, the development of a theory of human perfection can sometimes be seen as a catalyst for an author's movement away from a strong anthropological dualism. One cannot consistently be an anthropological dualist (i.e., hold an anthropologically dualistic theory) and have a theory of human perfection without it implying a negative valuation of man's material nature. The terms 'anthropological dualism' and 'anthropological monism' are often applied to a philosopher on the basis of his or her anthropological description of the structure of human beings, without taking into consideration the place that the author gives to our material nature in the achievement and enjoyment of human perfection. I maintain, however, that in order to properly assess an author's anthropological statements about the nature of human beings it can sometimes be beneficial to examine them in the light of statements (or attitudes) about the role that our materiality plays in the development of human perfection in order to see how accurately the author's valuation of human materiality corresponds to those anthropological statements. (Abstract shortened by UMI.)
Keywords: Philosophy.